“The Joys of Motherhood” of an African Woman: A Mirage - et. al., Siva R, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Quest for identity is one phenomenon of postcolonialism that led way for the emergence of Women writers portraying the indigenous women of their society who were denied the authorial voice in the male-dominated society. Africa African woman literature has always been discussed elaborately not only among ‘White’ but also among fellow African women writers and critics across the globe. Emecheta was one such writer whose work has been criticized for writing after settled in the western country, UK (the colonizer). The readers from third world nations may agree with Emecheta’s call for the necessity to redefine Women’s identity under the African identity. Buchi Emecheta to that reverence has always through her strong woman characters never failed to express the state of the African women and their limitations in social life. Emecheta has always recorded her protagonists' struggle for equality in a male-dominated society. Through the study of her novel The Joys of Motherhood, an attempt is made to explore her perception of Motherhood and explain how she portrays it to the African context where traditions and communal ties are deeply rooted in the Nigerian Ibo society.